Transformation of Regional Revenue Service Quality Based on Good Governance in Supporting Education Development in Sigi Regency - Andi Murfiqien Latjuba; Abdul Rivai; Intam Kurnia; Mustainah (Lembaga Bale Literasi, 2026)
This study examines how regional revenue governance in Sigi Regency, Central Sulawesi, aligns with good governance principles and what its contribution is to education sector development. Local own-source revenue (PAD) consistently accounts for only 5–7% of total regional income, while total revenue grew from approximately Rp 1.02 trillion in 2020 to Rp 1.41 trillion in 2024. The study employed a qualitative descriptive approach, gathering data through in-depth interviews with eighteen informants across the Regional Secretary’s Office, the Regional Financial Management Agency (BPKD), the Education Office, the Regional Legislative Council (DPRD), village heads, and community members. Documents including APBD reports, LKPD financial statements, and BPK audit records were also analysed. Triangulation of sources and methods ensured data validity. Findings reveal that the transparency and accountability dimensions have shown meaningful progress through routine financial reporting and BPK audits, with education budget realization rates consistently above 95%. However, community participation in budget planning remains procedural rather than substantive, and geographic inequities in education quality between urban and remote sub-districts persist despite improving aggregate indicators. This study introduces the ‘Governance Transformation’ framework as a novel theoretical contribution, arguing that revenue governance quality not budget volume alone is the primary determinant of education development outcomes in resource-constrained regional governments. The study recommends restructuring participatory mechanisms, adopting geographic need indices in budget formulas, developing community fiscal literacy programs, and piloting community-based education expenditure monitoring systems.